Threatening property : race, class, and campaigns to legislate Jim Crow neighborhoods - Herbin-Triant, Elizabeth A. (Columbia studies in the history of U.S. capitalism., 2019)
Elizabeth Herbin-Triant investigates early-twentieth-century campaigns for residential segregation laws in North Carolina to show how the version of white supremacy supported by middle-class white people differed from that supported by the elites. Class divides halted Jim Crow from mandating separate neighborhoods for black and white southerners